Earnings forecasts errors in Malaysian IPO prospectuses: Evidence and explanations - Ammer, Mohammed Abdullah; Ahmad Zaluki, Nurwati Ashikkin (Canadian Center of Science and Education, 2014)
This paper seeks to answer the questions concerning the current level of bias and accuracy associated with the IPO earnings forecasts and the explanations behind forecasts errors.Using 190 Malaysian IPOs, we found that the Malaysian IPO earnings forecasts during the period of study (2002-2012) were pessimistic (i.e., the earnings forecasts were underestimated), proposing that Malaysian IPO directors are, averagely unbiased and cautious forecasters.Moreover, we found the percentage of accuracy of Malaysian IPO earnings forecasts to be unsatisfactory.However, the percentage shows some improvement for the accuracy of earnings forecasts over time.Further, content analysis was used to explore the explanations provided behind the forecasts errors.This study found that, the number of provided explanations in first published annual report of IPO company was greater when the management of IPO companies were more optimistic in making their earnings forecasts (i.e., the earnings forecasts were over forecasted) and when the forecasts errors were large.These results have implications for the capital market participants like regulators and investors.